1/2(18x+2)=3(3x-2)-3(x-7)

Simple and best practice solution for 1/2(18x+2)=3(3x-2)-3(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/2(18x+2)=3(3x-2)-3(x-7) equation:


x in (-oo:+oo)

(1/2)*(18*x+2) = 3*(3*x-2)-(3*(x-7)) // - 3*(3*x-2)-(3*(x-7))

(1/2)*(18*x+2)-(3*(3*x-2))+3*(x-7) = 0

(1/2)*(18*x+2)-3*(3*x-2)+3*(x-7) = 0

1/2*(18*x+2)-3*(3*x-2)+3*(x-7) = 0

1/2*(18*x+2)-3*(3*x-2)+3*(x-7) = 0

3*x-21+7 = 0

3*x-14 = 0

3*x-14 = 0

3*x-14 = 0 // + 14

3*x = 14 // : 3

x = 14/3

x = 14/3

See similar equations:

| 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 | | k*k^12= | | 4x^2+7x=6 | | a^4-6a^2+5=0 | | 6+2(1+2x)=29-3x | | 2x-7(3-2x)=11 | | 2((1.5+2)+(1.5+3))=16 | | 154=4x^2+26x+40 | | -4+4x=-8 | | 2((x+2)+(x+3))=16 | | n+6=19 | | y=3x-1-4 | | (u+3)(2u-1)=-3 | | 8(4-6)=4(8x+7) | | 2(3t-8)-4t=30 | | 2(3t+8)-4t=10 |

Equations solver categories